Urinary Tract Injury at Benign Gynecologic Surgery and the Role of Cystoscopy: A Systematic Review and Meta-analysis. Issue 6 (December 2015) - Teeluckdharry, Brahmananda; Gilmour, Donna; Flowerdew, Gordon
Abstract : OBJECTIVE: To calculate the rates of urinary tract injury detected during and after benign gynecologic surgery. To explore the role of routine intraoperative cystoscopy and determine if it helps in reducing injuries detected postoperatively. DATA SOURCES: We conducted a literature search for urinary tract injuries at benign gynecologic surgery in PubMed, EMBASE, ClinicalTrials.gov, and Web of Science from January 2004 to August 2014. We combined our results with a database from a previously published systematic review to include earlier studies. METHODS OF STUDY SELECTION: A total of 79 studies met our inclusion criteria. Excluded were letters to the editor, studies involving only selective cystoscopy in higher risk patients, case reports, and reports that included injuries resulting from obstetric or oncologic procedures. TABULATION, INTEGRATION, AND RESULTS: Data from each report were classified according to type of surgery into vaginal hysterectomy, abdominal hysterectomy, laparoscopic hysterectomy, other (nonrobotic) gynecologic and urogynecologic surgery, robotic hysterectomy, and other robotic gynecologic and urogynecologic surgery. We determined the ureteric and bladder injury rates for each surgery type from studies in which routine intraoperative cystoscopy was performed and separately from studies in which it was not performed. Intraoperatively detected rates of ureteric and bladder injury were markedly higher with routine intraoperative cystoscopy. We obtained an adjusted ureteric injury rate of 0.3% and a bladder injury rate of 0.8%. The estimated postoperative ureteric injury detection rates per 1, 000 surgeries were 1.6 without routine cystoscopy and 0.7 with routine cystoscopy. Postoperative bladder injury detection rates per 1, 000 surgeries were 0.8 without routine cystoscopy and 1.0 with routine cystoscopy. CONCLUSION: Although routine cystoscopy clearly increases the intraoperative detection rate of urinary tract injuries, this systematic review of 79 mostly retrospective studies shows that it does not appear to have much effect on the postoperative injury detection rate. Abstract : Cystoscopy clearly increases the intraoperative detection rates for ureteric and bladder injuries but fails to provide any meaningful reduction in postoperatively detected injuries.